Albert Oehlen big paintings by me with small paintings by others - Oehlen, Albert 1954- (Mousse Publishing, 2021)
The artist as collector: Albert Oehlen's own artworks nail-to-nail with masterpieces from his personal collection.00The dual role of artist-collector is always an exciting coupling, and when the artist-collector is as elusive and discreet as Albert Oehlen, it is downright seductive. Albert Oehlen "big paintings by me with small paintings by others" - published on the occasion of the homonymous exhibition at the MASI Lugano in 2021 - witnesses Oehlen as an exhibited artist, a curator, and a collector. For the first time in such an extensive form, many of his own artworks are nail-to-nail with masterpieces from his collection. He devised a precise exhibition path in close collaboration with Francesca Benini and Christian Dominguez, and the catalogue reflects this precious dialogue. The connections between Oehlen's and the artists in his collection speak for themselves; readers will readily spot the many and various alignments in terms of their ideas about art and the big questions they seek to answer
Catalog of an exhibition held at the MASI, Lugano, Switzerland, September 5, 2021 - February 20, 2022
Keywords: Oehlen, Albert / 1954- / Exhibitions; Oehlen, Albert / 1954- / Art collections / Exhibitions; Art, Modern / 20th century / Exhibitions; Art, Modern / 21st century / Exhibitions; Art / Private collections / Exhibitions; Art / 20e siècle / Expositions; Art / 21e siècle / Expositions; Art / Collections privées / Expositions; Oehlen, Albert / 1954-; Art, Modern; Art / Private collections; 1900-2099; Exhibition catalogs; Ausstellungskatalog